Inovasi Pembelajaran Kitab Kuning Di Pesantren Dalam Penguatan Literasi Keagamaan - Daulay, Ronna Sari; Siregar, Meldyana Priadina; Panggabean, Hadi Saputra (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This research aims to analyze the forms of innovation in the teaching of Kitab Kuning in Islamic boarding schools (Pesantren) to strengthen religious literacy. The study employs a library research approach, utilizing literature sources such as journals, books, dictionaries, documents, magazines, and other references. The research method involves a literature review. The results indicate that Pesantren is capable of producing students proficient in Arabic language and fundamental knowledge of religious studies. Various innovations can be implemented to enhance religious literacy, such as the use of technology through e-learning and online forums. Additionally, innovations in teaching models or methods, such as the ArRumuz method, which facilitates quick reading of religious texts, and problem-based learning methods, involving the study of issues in society, can contribute to strengthening religious literacy. Moreover, innovations in extracurricular activities, including programs like Qira’atul Kutub tutoring, Qira’atul Kutub study sessions, and achievement award and art performance programs, are also noteworthy.